A Systematic Literature Review on Extended Reality: Virtual, Augmented and Mixed Reality in Working Life - Vasarainen, Minna; Paavola, Sami; Vetoshkina, Liubov (International Journal of Virtual Reality, 2021)
Extended reality (XR), here jointly referring to virtual, augmented, and mixed (VR, AR, MR) reality, is becoming more common in everyday working life. This paper presents a systematic literature review of academic publications on XR indicating changes in practical organization of work. We analyse both application areas of XR and theoretical and methodological approaches of XR research. The review process followed the PRISMA statement. Design, remote collaboration, and training were the main application areas of XR. XR enabled overcoming of obstacles set by time and space, safety, and resources by mediating experience of space. Research on XR applications in actual working life settings is yet relatively rare and covers primarily three areas: collaboration, evaluation of knowledge transfer, and work practices. Virtual reality was the most common form of applied XR, although the hardware used varied case by case. We identified four research areas regarding XR: collaboration, work practices, and evaluation of knowledge transfer, which somewhat followed the application areas. We did not find XR-specific methodologies in the reviewed articles, only few recent studies used novel ways of collecting research material, such as recording the movement in virtual reality. For now, XR still holds significant potential rather than clearly confirmed general advantages in working life.